Categorization in infancy: labeling induces a persisting focus on commonalities. Issue 5 (5th November 2015) - Althaus, Nadja; Plunkett, Kim
Abstract: Recent studies with infants and adults demonstrate a facilitative role of labels in object categorization. A common interpretation is that labels highlight commonalities between objects. However, direct evidence for such a mechanism is lacking. Using a novel object category with spatially separate features that are either of low or high variability across the stimulus set, we tracked 12‐month‐olds' attention to object features during learning and at test. Learning occurred in both conditions, but what was learned depended on whether or not labels were heard. A detailed analysis of eye movements revealed that infants in the two conditions employed different object processing strategies. In the silent condition, looking patterns were governed exclusively by the variability of object parts. In the label condition, infants' categorization performance was linked to their relative attention to commonalities. Moreover, the commonality focus persisted after learning even in the absence of labels. These findings constitute the first experimental evidence that labels induce a persistent focus on commonalities. Abstract : Twelve‐month‐old infants were familiarized with a novel object category in silence or with labels. Infants succeeded in forming a new category in both conditions. However, the processes underlying category formation differ when familiarization objects are presented with or without labels. In the absence of labels infants' attention is drawn to variability in category features. The presence of labels promotes attention to the commonalities between category exemplars.